1990
DOI: 10.21273/jashs.115.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuations of Some Enzymes Relating to Sucrose and Sorbitol Metabolism in Peach Fruit

Abstract: Sugar levels and composition were determined in developing `Hakuto' peach (Prunus persica Batsch var. vulgaris Maxim.) fruit. Glucose and fructose in nearly equal amounts were the predominant sugars detected during the early stage of development. Sucrose subsequently began to accumulate and was the predominant sugar in mature fruit. Sorbitol remained at a low level throughout development. The large increase in the amount of sucrose was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 15 publications
(9 reference statements)
8
86
1
Order By: Relevance
“…High invertase activity in peach fruit corresponded to the time when cell division was occurred Acid invertase activity increased in mature fruit when sucrose was also accumulating. This relationship indicates that sucrose accumulation in mature peach fruit was not the result of the reduction of acid invertase activity [32]. Similar results were represented in muskmelon [29,33] and kiwifruit [10] that the AI and NI activity patterns declined during fruit development.…”
Section: Enzyme Activities In Sucrose Metabolismsupporting
confidence: 74%
“…High invertase activity in peach fruit corresponded to the time when cell division was occurred Acid invertase activity increased in mature fruit when sucrose was also accumulating. This relationship indicates that sucrose accumulation in mature peach fruit was not the result of the reduction of acid invertase activity [32]. Similar results were represented in muskmelon [29,33] and kiwifruit [10] that the AI and NI activity patterns declined during fruit development.…”
Section: Enzyme Activities In Sucrose Metabolismsupporting
confidence: 74%
“…The predominant sugar in peach was sucrose (106.39 mg g -1 ), which were in 197 agreement with Moriguchi et al (1990). It was reported that sucrose was the major 198 component (> 70%) of total accumulated sugars in mature fruit, and sorbitol content 199 was about 5 mg g -1 fresh weights and comprised 4% of total sugars in mature fruit.…”
Section: Application For the Determination Of Sugars In Fruitssupporting
confidence: 72%
“…The first occurs in young fruit and the second at maturity [29, 40]. In this article, we focused on the quality of fruits at mid to late stages of development.…”
Section: Discussionmentioning
confidence: 99%